2018
DOI: 10.1097/sap.0000000000001432
|View full text |Cite
|
Sign up to set email alerts
|

Skin Graft Fixation Using Hydrofiber (Aquacel® Extra)

Abstract: The use of hydrofiber for skin graft fixation was effective and technically very simple. Splints were not required with this method, decreasing the medical waste created and increasing patient comfort. We suggest that this is an excellent alternative for skin graft fixation while at the same time decreasing our carbon footprint as surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Longer operative time is one of the technical disadvantages of the conventional tie-over bolster technique due to the additional materials and application steps involved [4]. Akihiko et al suggested the use of a polyurethane foam and elastic tapes to shorten the operative time, reduce medical waste, and produce likely graft outcomes, instead of using the conventional continuous sutures and knots on bolsters [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longer operative time is one of the technical disadvantages of the conventional tie-over bolster technique due to the additional materials and application steps involved [4]. Akihiko et al suggested the use of a polyurethane foam and elastic tapes to shorten the operative time, reduce medical waste, and produce likely graft outcomes, instead of using the conventional continuous sutures and knots on bolsters [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique has some disadvantages for both patients and clinicians. Patients may experience postoperative pain due to the tension of the bolster sutures and tearing pain during the removal of the tie-over dressing [4]. Postoperative pain is highly related to the tension caused by the silk or nylon sutures used in the tie-over bolster technique, and tearing pain is mainly due to the adhesion of the inner layer of the petrolatum gauze to the tissues [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review aimed to determine the effects of different methods on venous leg ulcer debridement reported hydrofiber dressings are less superior than biocellulose in a total mean reduction in ulcer size (Gethin et al, 2015). The results of a retrospective study showed that the use of hydrofiber Aquacel Extra for skin graft fixation was effective and technically very simple to use in the clinical setting (Yen et al, 2018). More complex dressing, such as silver containing hydrofiber dressing Aquacel Ag, has been reported to promote healing of partial thickness burns in pediatric patients (Lau et al, 2016).…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%
“… 1 Numerous methods for fixation with tie-over bolster, negative pressure, tissue glue, and others are found in the literature because immobilization is essential to prevent graft loss. 3 However, there is a high rate of graft loss that is still unreported.…”
mentioning
confidence: 99%